IPTEKS LAPORAN ARUS KAS SEBAGAI PENGUKUR PENILAIAN KINERJA KEUANGAN PADA PT. BANK SULUTGO - Kakasih, Gita Gabriella; Kodong, Tessa Isabel; Mawikere, Lidia M. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT. Bank SulutGo Headquarters is located at Jl. Sam Ratulangi no.9, north wenang, wenang, Manado City, North Sulawesi. Which was established on March 17, 1961 with the name of the Central North Sulawesi Regional Development Bank, on April 14, 1999 the regional development bank changed its name to PT. Bank Sulut, and September 23 2015 changed to PT. North Sulawesi Gorontalo regional development bank (PT. Bank SulutGo).In general, companies only think of big and fast profits by doing anything to achieve the desired target of the company, without thinking about the impact in the future. But gradually the company must realize that every activity must be carried out with a mature calculation taking into account the risks that must be faced. Financial performance is an analysis conducted by the company to find out where the operational activities are by using the rules in financial implementation effectively and efficiently. In this case the cash flow report at PT. Bank SulutGo has been running effectively and efficiently, so that the company can be more advanced in the future can be used as input for the company the need for efficiency to avoid undesirable things such as avoiding losses and also reducing unused cash.Keywords: cash flow statement, financial performance